Aggregation of human platelets by commercial preparations of bovine and porcine antihaemophilic globulin - Forbes, C. D. (1972)
Infusion of commercial preparations of porcine and bovine antihaemophilic globulin into three haemophilic patients produced transient thrombocytopenia. This platelet-aggregating activity has been shown to be present in a wide range of animal plasmas and is related to the fibrinogen fraction. The mechanism of platelet aggregation by animal fibrinogen is discussed and some inhibitors of the reaction are described.